Une nouvelle gouvernance : une condition nécessaire à la reprise économique en Irlande ? - Anne Groutel (Revue LISA)
The severe crisis which broke out in Ireland in 2007 spurred economists, public intellectuals, economic journalists and even a retired banker to write books on this topic. We have selected a sample of the works published when the crisis was at its worst in Ireland with a view to identifying common threads, themes and solutions. First of all, even if their authors concede that the world economic crisis had an impact on the country’s economy, they concur on the fact that the causes of the crisis in Ireland are mainly endogenous and that those in power were largely responsible for the country’s plight. However, those writers share the belief that lessons must be drawn from the crisis, which they view as a “necessary evil”, in order to steer the country out of the economic doldrums and make a fresh start, on a sounder basis. But the conditions necessary to “good governance” are clearly felt to be missing. We will highlight the remedies they propose to resort to in order to reform public governance in Ireland and whether this implies more government involvement in the economy or even an overhaul of the Irish economic system. In February 2011, a Fine Gael-Labour coalition succeeded Fianna Fáil at the helm of the country. In the last section of this paper, we will assess to what extent this government took on board the expectations expressed in this selection of books. With the benefit of hindsight, is it still fair to say that reforming public governance in Ireland is a prerequisite to economic recovery?